Konstribusi Kemampuan Merancang Pembelajaran Terhadap Efektivitas Pembelajaran Dosen STKIP-PGRI Sumatera Barat. Tesis. Program Pascasarjana Universitas Negeri Padang. - Edi Suarto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
This study aims to reveal the contribution Designing Learning Ability Learning Effectiveness Against Lecturer STKIP-PGRI West Sumatra. The hypothesis of the study is a contribution to effective learning capabilities designed an instructional faculty PGRI-STKIP West Sumatra, West. This study uses a total sampling involving subjects were 71 lecturers. They are professors and lecturers PNSD collected through questionnaires and student grades. The data collected is then analyzed statistically using correlation analysis and regresi.Hasil analysis showed that: The ability to design learning has a significant contribution to the effectiveness of learning lecturer PGRI-STKIP West Sumatra amounting to 35.5%, based on above findings, it can be concluded that the ability to design learning contribute to the effectiveness of learning lecturer STKIP PGRI Sumatra.